Analysis of Good Corporate Governance and Intellectual Capital on Profitability Ratio - Fitrio, Rian Renaldi Muhamad; Norisanti, Nor; Saori, Sopyan (Dinasti Publisher, 2024)
Increased competition in business at this time is experiencing rapid development. This causes every company to have a strategy in competing so as not to experience bankruptcy and improve the company's financial performance. This study aims to determine the effect of Good Corporate Governance on Financial Performance and to determine the effect of Intellektual Capital on Financial Performance at Commercial and Conventional Banks listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022. The research method that researchers use in solving problems is descriptive and associative research methods with a quantitative approach. The population in this study were conventional bank companies listed on the Indonesia Stock Exchange in 2020-2022. The samples used in this study were 10 commercial bank issuers listed on the IDX in the 2020-2022 period. The data collection techniques used in this research are literature study and documentation. The data analysis technique in this study is the multiple linear regression statistical method using SPSS software version 25. The results showed that there was a negative and insignificant effect of Good Corporate Governance on the Profitability Ratio and there was a positive and insignificant effect between Intellectual Capital on the Profitability Ratio.